PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Muna, Tazkiyatul; Hendriawan, Deri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Beginning reading ability is a fundamental foundation for the learning success of students in the early grades of elementary school. Various studies indicate that low beginning reading ability remains a problem in Grade 1 elementary classrooms. One approach considered effective in addressing this issue is the Contextual Teaching and Learning (CTL) model. This study aims to systematically analyze the results of research related to the implementation of the contextual learning model in improving the beginning reading ability of Grade 1 elementary school students. The method used is a Systematic Literature Review (SLR) by examining research articles published between 2014 and 2024. Data sources were obtained from Google Scholar, SINTA, and accredited national journals. The results of the review show that the implementation of the contextual learning model consistently has a positive impact on improving students’ beginning reading abilities, including letter recognition, reading fluency, basic comprehension, and learning motivation. Therefore, the contextual learning model can be recommended as an effective alternative instructional strategy for teaching beginning reading in Grade 1 elementary school.